Contos infantis e brinquedos como ferramentas de ensino-aprendizagem de conceitos de dinâmica: uma sequência didática direcionada ao Ensino Fundamental e Médio - Praxedes, Jacqueline Maria de Oliveira (2019)
This work proposes to teachers of Elementary and Middle School a way of working Dynamic concepts through the use of children's stories and toys. Its purpose is to stimulate students' willingness to learn physics with tools that are easily accessible and part of their daily lives. As well, to stimulate the teachers to elaborate constructive classes, avoiding the traditionalism with ludic classes, that do not require complexity in its elaboration. For this, an educational product elaborated in the research perspective was developed, involving an experimental activity with analysis of concepts related to Physics, specifically Dynamics, in short stories and toys. The product was applied in six schools of the state network and one school of the municipal network in the municipality of Arapiraca, Alagoas. In this study, the teachers of the selected schools themselves received and applied the material in their classes of the 1st Year of High School and 9th Year of Elementary Education. Initially, the teachers mapped the previous knowledge of their students and then worked on the didactic sequence that was assigned to them. In the classes of the 1st Year of High School, two different sequences were applied, in the first one was used a toy and in the second a story. In the 9th grade classes, teachers used only one sequence, which varied between story or toy. The students and teachers answered for each sequence a pre-test and a post-test. As we will see below, the use of children's toys and stories has proved to be an excellent auxiliary tool in the teaching-learning process of the contents worked.